Fizkul'turnoe obrazovanie zapadnoi Sibiri: Sostoyanie i perspektivy - Potapov, V. N.; Smirnov, P. G. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The article is dedicated to the anniversary of physical culture faculty in Tyumen State University. The authors analyze the stages of the faculty's development for the last 10 years. They aquaint readers with the famous scientists, managers, teachers, coaches and athletes - whose biography is directly connected with that faculty.